The Influence of Social Media Towards Student Political Participation During the 2014 Indonesian Presidential Election - ANWAR KHOLID; RAHMAWATI HUSEIN; DYAH MUTIARIN; SEPTIYAN LISTIYA E. R (Jurnal Studi Pemerintahan, 2015)
This research attempts to examine the political participation of social media users particularly of Facebook and Twitter during the 2014 Indonesian presidential election. The data collection was performed through survey with accidental sampling methods. Samples were taken from population of undergraduate students of political and social sciences faculty at five universities in Yogyakarta namely UGM, UIN Sunan Kalijaga, UMY, UNY and UPN “Veteran” Yogyakarta. Using statistic descriptive,this research conceptualizes the political participation of social media users while the relations of social media and political participation is analyzed through OLS Regression. The findings indicated that the level of political participation of the social media users during the election was categorized as good. However, the facilities offered by the two social media applications were not maximally used to supporting political participation activities. On the other hand, the result OLS regression shows that there were positive and significant correlations and influences of social media towards the political participation of its users during the election even though the percentage was small.